Determinant Factors of Bullying in Adolescent - Endang Caturini Sulistyowati; Insiyah Insiyah; Febriana Sartika Sari (Indonesian Journal of Global Health Research, 2024)
Adolescence has great energy and turbulent emotions but rudimentary self-control. Many cases of bullying occur during this period due to internal and external factors. Identifying determinants and factors affecting bullying behaviour is crucial in preventing bullying incidents. Objective: The study aimed to identify the determinant factors of adolescent bullying behaviour. The design of this study used a correlation descriptive survey with a simple random sampling technique. The respondents are 7th-grade Senior High School students in Surakarta, with a total respondents 88 students. The instruments used were the Olweus Bully Victim Questionnaire, Rosenberg Self-Esteem Scale, personality questionnaire, self-actualization questionnaire, emotion regulation questionnaire, social support questionnaire, social media questionnaire, and DASS. The data analysis used the Pearson correlation (parametric data) and the Spearmen-rho test (non-parametric data). The results of the study indicated that the majority of respondents were female, which was 52.3%. There was no significant association between depression-anxiety-stress, self-actualization, personality, self-concept, family support, social media, and emotional regulation. Peer support has a significant relationship with bullying behaviour. Peer support tends to reduce the risk of bullying behaviour among adolescents. This result suggests that peers have a significant impact on bullying behaviour.